2021
DOI: 10.1007/s00223-021-00900-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Changes in Serum Levels of Intact Parathyroid Hormone and Sclerostin After a Single Dose of Zoledronic Acid: Results of a Phase 1 Pharmacokinetic Study

Abstract: Although changes in serum sclerostin levels at 12 months after infusion of zoledronic acid have been reported, the changes in sclerostin levels at earlier time points are poorly understood. We reanalyzed the study data of a previous phase 1 pharmacokinetic study and investigated the correlation between changes in sclerostin levels and relevant factors in calcium metabolism. A total of 24 Japanese female subjects with primary postmenopausal osteoporosis were administered a single 4- or 5-mg dose of zoledronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The same applies for the relationship between serum iPTH and osseous sclerostin expression, which may be largely driven by altered kidney function. It has also been reported that changes in iPTH occur more quickly than in serum sclerostin, which may, at least in part, explain the different trends in serum iPTH and sclerostin levels [ 46 ]. In addition, based on observations in both our rat study and human study, one may suggest that the changes in serum occur later than in bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The same applies for the relationship between serum iPTH and osseous sclerostin expression, which may be largely driven by altered kidney function. It has also been reported that changes in iPTH occur more quickly than in serum sclerostin, which may, at least in part, explain the different trends in serum iPTH and sclerostin levels [ 46 ]. In addition, based on observations in both our rat study and human study, one may suggest that the changes in serum occur later than in bone tissue.…”
Section: Discussionmentioning
confidence: 99%